Investigation on the Mechanical Properties of Flax/False Banana Hybrid Fiber-Reinforced Polymer Composite - Alelign Zelalem Biresaw; Belete Sirahbizu Yigezu (Advances in Materials Science and Engineering)
The intent of this research is to develop new material from flax and false banana fiber hybrid reinforced polymer composite using polyester resin as a matrix to replace synthetic fiber-reinforced polymer composites for automotive interior bodies. The composite samples were fabricated based on the weight percentage of fibers/matrix and the orientation of the fibers that were combined with Taguchi’s experimental design using the hand layup fabrication process. And also, single flax and single false banana fiber-reinforced polymer composite was fabricated with the same composition and orientation alone. The composite was tested for tensile and flexural strength properties, and it had been discussed and specimens were prepared according to ASTM standards. As a result, false banana showed better flexural strength than false banana fiber-reinforced composite for tensile strength, whereas the hybrid composites of 25% of flax, 15% of false banana, and unidirectional orientation have shown the maximum tensile and flexural strength with a value of 113.4 MPa and 167.88 MPa, respectively.